Antibacterial Activity of Endophytic Fungi Isolated from Pulai Leaves (Alstonia scholaris) - Rumalolas, Mira; Kotala, Sarmawaty; AF, Asyik Nur Allifah (Jurnal Biologi Tropis, 2024)
Extraction of active compounds from plants requires a lot of raw materials. Therefore, other alternatives are needed that can produce active compounds in a relatively fast time. One of them is the use of endophytic fungi. Endophytic fungi live in plant tissues including pulai (Alstonia scholaris) which is used as an ingredient in herbal medicine. Endophytic growths can create auxiliary metabolite intensifies that are like their host plants. The point of this examination was to decide the sorts of endophytic growths found on pulai leaves and their antibacterial action. This research is a qualitative research, where microscopic characteristics of fungi are observed using the slide culture method and antibacterial activity is tested using the modified Kirby Bauer method. The results of this research found 8 isolates of endophytic fungi, consisting of Neurospora sp1, Neurospora sp2, Paecilomyces sp, Acremonium sp, Fusarium sp, and 3 unidentified isolates. All endophytic fungi found on pulai leaves can inhibit the growth of Staphylococcus aureus and Escherichia coli with the highest inhibition zone diameter found in isolate K8 (Acremonium sp) at 3 cm for S. aureus and isolate K7 at 1.8 cm for E. coli.